The financial behavior of Malaysian public servants - Zafirah, Mohd Mansor (2014)
This study aims to examine the relationship between financial behavior among public servants in Putrajaya with the level of financial literacy and demographic characteristics of respondents. The study covers a population of about 1500 civil servants. A total of 167 respondents participated in this study. Descriptive analysis was performed to analyze the correlation analysis in order to examine the relationship between levels of financial literacy and financial behavior of Malaysian public servants. ANOVA and T-test technique used to study the significant differences in financial literacy between the demographic factors. The chi-square analysis also conducted to measure the relationship between financial knowledge and the demographic factors. The results show that there are correlation exists between the level of financial literacy and the financial behavior among Malaysian public servants. However, there were mixed results between the demographic factors and the level of financial literacy among the participants